2018
DOI: 10.3390/en11041013
|View full text |Cite
|
Sign up to set email alerts
|

Study on Variation of Internal Heat Gain in Office Buildings by Chronology

Abstract: Abstract:The additional process of load calculation during the retrofit of heating, ventilation, and air conditioning (HVAC) equipment has been generally omitted in Korea, in recent years. Instead, a simple replacement of HVAC equipment, based on existing HVAC capacities, has been used, which is limited when taking the variation of internal heat gain into consideration, due to changes in the consumption power due to light and office automation (OA) equipment in recent years. Thus, this study aimed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The internal heat sources were OA equipment, lighting, and human body heat. In a preceding study [6], the loads were calculated based on literature and catalogues. Table 6 shows the result of a survey on electricity consumption per unit of OA equipment and lighting.…”
Section: Results Of the Survey On The Internal Heat Loadmentioning
confidence: 99%
See 4 more Smart Citations
“…The internal heat sources were OA equipment, lighting, and human body heat. In a preceding study [6], the loads were calculated based on literature and catalogues. Table 6 shows the result of a survey on electricity consumption per unit of OA equipment and lighting.…”
Section: Results Of the Survey On The Internal Heat Loadmentioning
confidence: 99%
“…However, as the service life of lighting and OA equipment ranges from three to five years, they are replaced frequently, which contributed to changes in the internal heat load. A preceding study [6] showed the quantitative picture of such changes.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations